2019
DOI: 10.1080/15384101.2019.1580493
|View full text |Cite
|
Sign up to set email alerts
|

miR-185 silencing promotes the progression of atherosclerosis via targeting stromal interaction molecule 1

Abstract: Background: Atherosclerosis (AS) is a major risk factor for cardiovascular disease. microRNAs play a key role in gene regulation in the formation and development of atherosclerotic plaques. Herein, the role and target gene of miR-185 in AS were explored. Materials and methods: Cell viability, migration and invasion were examined by cell counting kit-8 (CCK-8) and transwell assay. The relative luciferase activity was measured by luciferase reporter assay. The levels of miR-185, STIM1, vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…In recent years, microRNAs (miRNAs) have been recognized as important molecules in biological processes and are associated with various human diseases ( 22 ). For example, Fang et al ( 23 ) reported that miR-185 promoted the progression of atherosclerosis by targeting STIM1. A study by Liu et al ( 24 ) demonstrated that miR-34a promoted renal fibrosis by downregulating Klotho in tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, microRNAs (miRNAs) have been recognized as important molecules in biological processes and are associated with various human diseases ( 22 ). For example, Fang et al ( 23 ) reported that miR-185 promoted the progression of atherosclerosis by targeting STIM1. A study by Liu et al ( 24 ) demonstrated that miR-34a promoted renal fibrosis by downregulating Klotho in tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of TCDD-and PCB-induced atherosclerosis has been well characterized by many studies [21,23,39,40]. Emerging data continue to demonstrate the participation of miRNAs in atherosclerosis [41][42][43] and in biological responses induced by environmental pollutants [44][45][46]. However, there have been no previous reports on miRNA expression in TCDD-and PCB-induced atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…And ectopic STIM1 expression impaired miR-641-mdiated effects on cell proliferation and metastasis in ox-LDL-stimulated VSMCs. The evidences from our research implicated STIM1 served as a promoter in the progression of ox-LDL-stimulated VSMCs, which was proved by the existed evidences [ 43 , 44 ]. In the meantime, the above data implied that miR-641 repressed the progression of VSMCs stimulated by ox-LDL via binding to STIM1.…”
Section: Discussionmentioning
confidence: 53%